Paul Auster’s The Locked Room as a critique of the hyperreal - Torkamaneh, Pouria; Taghizadeh, Ali (Penerbit Universiti Kebangsaan Malaysia, 2016)
Auster’s The Locked Room (1986) presents a protagonist in a desperate quest for a lost character whose absence functions as the only significant storyline to which the narrative unfolds. Although, stylistically, the entire plot revolves around the disappeared Fanshawe, nowhere in the narrative can the reader identify with certainty any traces of his actual existence. Fanshawe never appears in the story, but all the characters and their lives centre firmly upon him, thereby creating the illusion that without his appearance their lives can never be fully restored nor can they make any real sense. Taking into account Baudrillard’s notion of hyperreality, this research tries to demonstrate that what Auster’s characters go through is living obsessively with a nonpresent inaccessible Fanshawe whose abrupt disappearance leaves no clue of his existence, but just a lost memory which haunts the characters’ deepest senses of reality. This claim especially strengthens itself in the end, when the reader finds out that it all has been Fanshawe’s plot to keep his family and friend in dark in order to completely vanish from the realm of the real.